General Kiszczak mowi-- prawie wszystko - Beres, Witold; Skoczylas, Jerzy (Warszawa : Polska Oficyna Wydawnicza "BGW", 1991)
A biographical interview with one of the most powerful military personalities in Poland.
Keywords: Kiszczak, Czeslaw; Politicians -- Poland -- Biography; Poland -- Politics and government -- 1980-1989.